2014
DOI: 10.1016/j.amjmed.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Mass Index As a Predictor of Longevity in Older Adults

Abstract: Purpose Obesity (as defined by body mass index) hasn’t been consistently associated with higher mortality in older adults. However, total body mass includes fat and muscle which have different metabolic effects. This study was designed to test the hypothesis that greater muscle mass in older adults will be associated with lower all-cause mortality. Methods All-cause mortality was analyzed by the year 2004 in 3,659 participants from the National Health and Nutrition Examination Survey III, who were 55 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
198
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(206 citation statements)
references
References 36 publications
4
198
0
4
Order By: Relevance
“…Skeletal muscle is the organ where most of the glucose metabolism occurs, and studies have shown that increased muscle mass is associated with better insulin sensitivity, better glucose metabolism, and lower rates of type 2 diabetes mellitus and cardiovascular events 20, 21, 22. Likewise, sarcopenia, defined as a loss of muscle mass and associated with frailty and overall decreased functionality and increased mortality, could have harmful effects in patients with CAD, as our results suggest 23, 24, 25…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle is the organ where most of the glucose metabolism occurs, and studies have shown that increased muscle mass is associated with better insulin sensitivity, better glucose metabolism, and lower rates of type 2 diabetes mellitus and cardiovascular events 20, 21, 22. Likewise, sarcopenia, defined as a loss of muscle mass and associated with frailty and overall decreased functionality and increased mortality, could have harmful effects in patients with CAD, as our results suggest 23, 24, 25…”
Section: Discussionmentioning
confidence: 99%
“…Next, we investigated whether activation of 4E-BP1 in skeletal muscle also protects mice from age-induced metabolic dysfunction. The loss of skeletal muscle mass (sarcopenia) with age is associated with higher mortality in the elderly (51)(52)(53). Sarcopenia often leads to frailty, resulting in a decreased metabolic rate and increased risk of insulin resistance (54).…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that both cardiorespiratory fitness (CRF) [1] and peak muscular power output [4] decline with advancing age. These declines are powerful predictors of both independence [2], and risk of morbidity [5]. Indeed, a major obstacle to achieving increased health span, reduced morbidity and optimal longevity in individuals is the decline in physiological function that accompanies advancing age [6].…”
Section: Introductionmentioning
confidence: 99%